Biodegradation of 2, 5‐dimethylpyrazine in gas and liquid phase by the fungus Fusarium solani. Issue 6 (24th September 2021) - Araya, Blanca; Diaz, Camilo; Martín, Jessica San; Vergara‐Fernández, Alberto; Aroca, Germán; Scott, Felipe
Abstract: BACKGROUND: Alkylpyrazines are odorous compounds conferring pleasant aromas to baked and roasted foods. However, they are also emitted during food processing, creating a nuisance for the operators and the community. Only a few bacterial isolates have been shown to degrade 2, 5‐methylpyrazine (DMP), as a model alkylpyrazine. This work aimed to study the ability of DMP biodegradation by the filamentous fungus Fusarium solani . RESULTS: Evidence of the degradation of DMP was collected in axenic cultures of F. solani in liquid mineral medium and over a saturated solid support using DMP as the sole carbon and energy source. DMP was used for growth as evidenced by the formation of an abundant aerial mycelium over a solid support, accompanied by the production of 70 ppm CO2 mg −1 dry biomass, and by its consumption in liquid media at a rate of 58.3 mg g −1  biomass h −1, a value comparable to those reported for bacteria. A non‐axenic biofilter was mounted, fed with a DMP‐laden air stream, and operated for 40 days. The maximum DMP elimination capacity achieved was 8.5 g m −3  h −1 at an inlet load of 11.3 g m −3  h −1 (an 80% relative efficiency). CONCLUSION: Fusarium solani uses DMP as a carbon source, showing great potential for its abatement in a biofilter. High‐throughput DNA sequencing of biofilter samples showed that it was the most representative member of the community, with a relative abundance surpassing 97%, indicating that it played a pivotal role in the biofilter. © 2021 Society of Chemical Industry (SCI).